2010
DOI: 10.1128/aem.02291-09
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Air Temperature and Relative Humidity on Coronavirus Survival on Surfaces

Abstract: Assessment of the risks posed by severe acute respiratory syndrome (SARS) coronavirus (SARS-CoV) on surfaces requires data on survival of this virus on environmental surfaces and on how survival is affected by environmental variables, such as air temperature (AT) and relative humidity (RH). The use of surrogate viruses has the potential to overcome the challenges of working with SARS-CoV and to increase the available data on coronavirus survival on surfaces. Two potential surrogates were evaluated in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

60
705
7
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 724 publications
(805 citation statements)
references
References 29 publications
60
705
7
9
Order By: Relevance
“…This study, studies on SARS-CoV (discussed previously), and studies on other coronaviruses suggest that they survive on environmental surfaces for a sufficient time to allow fomite transmission. 102 Studies on inactivation of SARS-CoV (previously discussed) and other coronaviruses are inactivated within 1 minute by phenolics (1.3-2.0 log10 reduction) and 70% ethanol (3.2-3.9 log10 reduction). 103 Hypochlorite with a 1:00 dilution, had a 1 minute decrease of <1 log10.…”
Section: Similarities and Differences Between Sars And Mersmentioning
confidence: 98%
“…This study, studies on SARS-CoV (discussed previously), and studies on other coronaviruses suggest that they survive on environmental surfaces for a sufficient time to allow fomite transmission. 102 Studies on inactivation of SARS-CoV (previously discussed) and other coronaviruses are inactivated within 1 minute by phenolics (1.3-2.0 log10 reduction) and 70% ethanol (3.2-3.9 log10 reduction). 103 Hypochlorite with a 1:00 dilution, had a 1 minute decrease of <1 log10.…”
Section: Similarities and Differences Between Sars And Mersmentioning
confidence: 98%
“…16 Since other human coronaviruses do not share the unusual survival properties of SARS-CoV, TGEV and mouse hepatitis virus (MHV) are often used as surrogates. 26,43,45 No study has tested more than one strain of SARS-CoV or MERS-CoV. However, some studies have tested more than one strain of influenza, highlighting considerable strain variation.…”
Section: Survival On Dry Surfacesmentioning
confidence: 99%
“…32,33,39 In all studies that tested varying temperature and RH, lower temperature and RH favoured the survival of both coronaviruses and influenza. 16e18, 26,35,36,38 Different methods have been applied to detect virus e most often cell culture assays but also RNA detection using polymerase chain reaction (PCR) or indirect methods such as fluorescence or haemagglutinin assays. 27,33,34,37,40 Intact viral RNA appears to remain detectable on surfaces for longer than viruses that retain the ability to infect cells.…”
Section: Survival On Dry Surfacesmentioning
confidence: 99%
“…Multiple studies on CoVs other than MERS-CoV have demonstrated that these viruses can remain viable for days to weeks on environmental surfaces. 88,89 Survival is enhanced at low temperatures (ie, 4°C vs 20°C). 89…”
Section: Environmental Contamination and Survivalmentioning
confidence: 99%